Terceiro setor: uma visão crítica - Meneses, Ana Paula Machado Costa (2013)
The thesis is limited to the contextualization of the Third Sector and its most relevant aspects: public promotion and control. Initially are appreciated the issues relating to the not-for-profit sector of civil society within the evolution of the democratic and social State governed by the rule of law, and as a result of the reform of the State. Later on, it searches the identification of non-profit organizations that make up the Third Sector through concepts constructed by doctrine. On the issue of public promotion of social interest entities, it exposes the existing forms in Brazilian legislation, namely, social subvention, social aid and contribution, on the basis of administrative law foreigner and Brazilian, emphasizing the legal instruments agreement, partnership contract and management contract , maintained between the public authorities and those entities, with basis on federal legislation. After all, it highlights the social control and control by results, through critical examination of administrative and legal mechanisms of control and supervision carried out by the Public Prosecutor Office and the Court of Auditors (General Accounting Office United States of America). In this way, the research is essentially literary and jurisprudential lifted from the legislation, doctrine, and jurisprudence regarding the Third Sector, by referring to books, magazines and articles in addition to the internet.